THE CONCEPT OF BUSINESS ACTIVITY AND ORGANIZATIONAL - LEGAL FORMS - Firuza Nabijonovna, Bayboboeva; Raxmatullo Alojonovich, Rashidov (International Journal of Psychosocial Rehabilitation, 2020)
In this article, matters about providing favorable legal and organizational conditions for active entrepreneurship, introducing innovative ideas and technologies, improving legal safeguards for the protection of business entities and mechanisms to prevent illegal interference in their activities, reducing administrative influence on economic sectors, and enhancing market governance mechanisms, providing reliable protection of rights and guarantees, development of private entrepreneurship and small businesses are mentioned.